Upaya Peningkatan Aktifitas dan Hasil Belajar Pendidikan Jasmani Pokok Bahasan Budaya Hidup Sehat Siswa Kelas XI IPA 1 SMAN 3 Kotabumi Tahun Pelajaran 2018-2019 Melalui Pemberian Tes Kecil di Awal Kegiatan Pembelajaran - mugi yanti (Universitas Muhammadiyah Kotabumi, 2020)
This research was carried out with the aim of increasing the activities and learning outcomes of Physical Education by giving small tests at the beginning of the learning process on the material of Healthy Living Culture for students of class XI IPA 1 SMA Negeri 3 Kotabumi in the 2018-2019 academic year. This study was designed in the form of classroom action research carried out on class XI IPA 1 students of SMAN 3 Kotabumi in the 2018-2019 academic year. The selected subject matter is Healthy Living Culture by implementing a small test at the beginning of the learning process and then observing whether there are changes in student learning outcomes in the material. The study was divided into 2 cycles, namely for healthy living exercise materials and the consequences of not implementing a healthy lifestyle. All cycles consist of planning, implementing and observing, and ending with reflection. Data collection techniques using cognitive tests and student attitude questionnaires obtained from each cycle, the results were analyzed whether there was an increase in each cycle. The results of this study indicate that by giving a small test at the beginning of the learning process on Healthy Living Culture material can help increase the number of students in class XI IPA 1 who score above KM. Student learning outcomes increased 32% from cycle I 50% to 82% in cycle II, while student activities based on questionnaires increased in cycle II where students were more disciplined, cooperative, polite and tolerant in learning. Thus it is concluded that giving a small test at the beginning of teaching and learning activities on Healthy Living Culture material can improve the learning outcomes of students in Class XI IPA 1 Physical Education at SMAN 3 Kotabumi in the 2018-2019 academic year.